PENGGUNAAN METODE ANALYTICAL HIERARCY PROCESS (AHP) DALAM MENENTUKAN PLATFORM ONLINE FOOD DELIVERY TERBAIK - Bonni Nurtanaya; Edhi Prayitno; Juarni Siregar; Muhammad Muharrom (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
Decision support system is one part of the benefits of information systems that can be a guide for users in determining the best choice from several available options. Some consumer considerations in making purchases online illustrate that there are factors that influence consumer decisions in making purchases of goods. This study refers to the level of decision and consumer satisfaction in choosing the best online food delivery service platform so that it can provide an alternative problem solving in making a decision. The use of the AHP (Analytical Hierarchy Process) method in this study was used to determine the choice of the best online food delivery platform from the 3 available options, namely Grabfood, Gofood and Shopeefood. Data collection by distributing questionnaires to 50 respondents aged 18-40 years to analyze and test the 5 (five) specified criteria including price, promotion, service, security and speed. Assessment of the selection of online food delivery service platforms with these criteria uses pairwise comparison scale with an importance level from 1-9 intervals. The research results based on the weight of each of these criteria, namely speed 0.161, security 0.253, service 0.251, promotion 0.174 and price 0.161 as well as the percentage of online food delivery platforms chosen by respondents are as follows: Grabfood 36.02%, Gofood 34.14 %, and Shopeefood 29.84%. From this study, it can be concluded that Grabfood is an online food delivery platform that is most in demand by the current millennial generation.